2019
DOI: 10.1155/2019/1741958
|View full text |Cite
|
Sign up to set email alerts
|

Optimum Solutions of Fractional Order Zakharov–Kuznetsov Equations

Abstract: In this paper, the Optimal Homotopy Asymptotic Method is extended to derive the approximate solutions of fractional order two-dimensional partial differential equations. The fractional order Zakharov–Kuznetsov equation is solved as a test example, while the time fractional derivatives are described in the Caputo sense. The solutions of the problem are computed in the form of rapidly convergent series with easily calculable components using Mathematica. Reliability of the proposed method is given by comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Recently, Sarwar et al extended the idea of OHAM fractional-order partial differential equations and used them for different problems having fractional-order derivatives [27,28]. Nawaz et al applied the suggested approach to the fractional-order Zakharov-Kuznetsov equations [29]. Likewise, Zada et al…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Sarwar et al extended the idea of OHAM fractional-order partial differential equations and used them for different problems having fractional-order derivatives [27,28]. Nawaz et al applied the suggested approach to the fractional-order Zakharov-Kuznetsov equations [29]. Likewise, Zada et al…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers used the proposed technique for different types of problems in literature. Iqbal et al implemented it for Klein-Gordon equations [19] and singular Lane-Emden type equation [20], Sheikholeslami et al used OHAM for the investigation of the laminar viscous flow [21], Hashmi et al obtained solution of Fredholm integral equations [22], and Nawaz et al obtained optimum solutions of fractional-order Zakharov-Kuznetsov Equations [23], three-dimensional Volterra integral equations [24], and fractional integro-differential equations [25]. We apply the method to obtain the approximate solution of a system of VIEs and test some numerical examples to show the effectiveness and accuracy of the method.…”
Section: Introductionmentioning
confidence: 99%